A comparative study of the methods of inclusion of pmu current phasor measurements in a hybrid state estimator - Chakrabarti, S.; Kyriakides, E.; Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
The paper compares three different methods of inclusion of current phasor measurements by phasor measurement units (PMUs) in the conventional power system state estimator. For each of the three methods, comprehensive formulation of the hybrid state estimator in the presence of conventional and PMU measurements is presented. The performance of the state estimator in the presence of conventional measurements and optimally placed PMUs is evaluated in terms of convergence characteristics and estimator accuracy. Test results on the IEEE 14-bus and IEEE 300-bus systems are analyzed to determine the best possible method of inclusion of PMU current phasor measurements.